Quantitative Analysis for the Change in Lengths of the Radius and Ulna in Missed Bado Type I Monteggia Fracture. Issue 10 (November 2020) - Oka, Kunihiro; Tanaka, Hiroyuki; Shigi, Atsuo; Abe, Shingo; Miyamura, Satoshi; Shiode, Ryoya; Kazui, Arisa; Murase, Tsuyoshi
Abstract : Background: In missed Monteggia fracture (MMF) cases, ulnar angulation and lengthening by osteotomy are required to reduce the dislocated radial head. This study aimed to clarify the abnormal discrepancy in length between the radius and ulna in MMF. We tested the hypothesis that the increase in the abnormal discrepancy in length between the radius and ulna relates with the duration of radial head dislocation. Methods: In total, 24 patients with MMF were studied and classified into 2 groups, according to the duration of radial head dislocation, including the early group (n=9, within 3 y) and the long-standing group (n=15, older than 3 y). The lengths of the radius (Lr) and ulna (Lu) were measured. The difference in length between the ulna and radius (DL=Lu−Lr) was calculated on both the affected (DLaff ) and normal (DLnor ) sides. DLnor −DLaff, which represented an abnormal discrepancy in both bones, was analyzed for correlation with the duration of radial head dislocation and the age at initial injury. Results: The affected and normal sides had no differences in the Lr of both the groups and in the Lu of the early group. However, in the long-standing group, Lu was significantly smaller in the affected side than in the normal side ( P =0.001). In the long-standing group, DLaff was significantly smaller, owing to decreased length of the ulna, than DLnor ( P =0.003). The DLnor −DLaff was positively correlated with the duration of radial head dislocation and was negatively correlated with the age at injury. Conclusions: In chronic MMF cases, the length of the ulna was shorter in the affected side than in the normal side. Therefore, ulnar lengthening is necessary to resolve this abnormal discrepancy and reduce the radial head. Because excessive ulnar lengthening has risks of postoperative complications, one of the surgical options is gradual ulnar lengthening or shortening osteotomy of the radius. Level of Evidence: Level III—Prognosis study.